District Magnitude and Representation of the Majority's Preferences: Quasi-Experimental Evidence from Popular and Parliamentary Votes - Marco Portmann; David Stadelmann; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2010)
Members of parliament have more effective incentives to cater for the majority's preferences when they are elected in districts with few seats in parliament rather than in districts with many seats. We empirically investigate this hypothesis by matching voting behavior on legislative proposals of Swiss members of parliament with real referenda outcomes on the same issues for the years 1996 to 2008. This quasi-experimental data allows us to identify the impact of electoral systems through district magnitude on how members of parliament represent citizens' preferences. We find systematic, statistically significant and economically relevant evidence that members of parliament from districts with few seats vote along the majority's preferences.
Keywords: D72; D70; H00; 330; Median Voter; Political Economy; Electoral Systems